Islam, the Arabs and Umayyad Rulers According to Theophanes the Confessor’s Chronography - Cecota, Błażej; Figat, Konrad (Studia Ceranea, 2012)
As the Chronography of Theophanes the Confessor includes a lot of information about the foreign states and tribes which were connected with the Byzantine Empire. It is legitimate, in the Author’s view, to analyse the account concerning Islam and the Arabs by this Byzantine author. Theophanes possessed detailed knowledge of the Arabs, Islam and Umayyad caliphs. He used, although presumably indirectly, some Muslim sources in his work. The argument which strongly proves this hypothesis is his precise description of inner clashes between the members of the ruling house, as well as of Arab civil wars. The article discusses how Theophanes (and presumably his sources) depicted not only the Arabs as an entity, but also the prophet Muhammad and some of the Umayyad caliphs (Muawiya, Walid I, Umar II, Hisham, Marwan II).